Examining recent mortality trends The impact of demographic change - Morgan, David (OECD Health Working Papers, 2023)
The pandemic resulted in a significant increase in the number of deaths in many OECD countries. With detailed data now available by age and sex, this OECD Health Working Paper examines the trends and differences in mortality patterns over the three-year span of the pandemic. While a simple comparison of the raw number of deaths with reference to a historical base period has proved to be an important and straightforward indicator to assess the overall impact of the pandemic, most OECD countries have undergone major changes in population size and structure. This paper reviews the methodology of calculating changes in mortality to take account of such demographic trends and, in producing a revised set of estimates using adjusted numbers of deaths, highlights some important variations in mortality across years, countries and age groups